2015
DOI: 10.3390/w7126656
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Epilithic Diatoms in Estuaries of the Korean Peninsula in Relation to Environmental Variables

Abstract: This study explores the relationships between environmental factors and the distribution of epilithic diatoms in 161 estuaries of three coastal areas on the Korean peninsula. We investigated epilithic diatoms, water quality, and land use in the vicinities of the estuaries during the months of May 2012, 2013 and 2014, because Korea is relatively free from the influences of rainfall at that time of year. We recorded 327 diatom taxa from the study sites, and the assemblage was dominated by members of the Navicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…During the study period, 566 taxa of epilithic diatoms were identified in 512 sites. These results determined a higher number of taxa than the 327 taxa found in 161 sites between 2012 and 2014 in a previous study [31], which appears to be the result of the present study having more survey sites than previous studies. With respect to dominant species, the Nitzschia genus appeared in over 38% of estuaries in the Korean Peninsula.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…During the study period, 566 taxa of epilithic diatoms were identified in 512 sites. These results determined a higher number of taxa than the 327 taxa found in 161 sites between 2012 and 2014 in a previous study [31], which appears to be the result of the present study having more survey sites than previous studies. With respect to dominant species, the Nitzschia genus appeared in over 38% of estuaries in the Korean Peninsula.…”
Section: Discussionsupporting
confidence: 45%
“…In Korea, aquatic ecosystem health assessments have been conducted every year since 2008, using epilithic diatoms for most of the rivers throughout the country [26]. However, there is very little information with respect to employing epilithic diatoms as indicator organisms for estuaries, as studies in Europe and Korea are very limited [27,28,29,30,31]. The majority of studies related to estuaries have concentrated on red-tide or eutrophication phenomena, which are caused by marine aquaculture or nutrients introduced into rivers, while other studies have focused mainly on ecological research of biological communities, such as phytoplankton, vegetation structure, fish, and benthic animals, including water quality [32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…and Navicula sp. These plankton species are considered to be indicators of good levels of dissolved oxygen concentration (Kim et al 2015). These types of dominant plankton species suggest that the water in the ponds is enriched with nutrients and has good water circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Colleagues from Ukraine, working within the framework of the development of a national marine strategy, are actively introducing a morphological and functional approach to assess the state of the environment using indices of the specific surface area of macrophytes and microalgae [24][25][26]. Integrated indices and comparative statistics, using various structural indicators of marine and estuarine ecosystems, is widespread [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, applying these approaches to assessing the state of marine ecosystems has not yet received widespread use due to the limited number of indicator species [20,21,32]. The combined approach of studying the species composition of algae and statistics in the coastal area has good examples of its application [28]. We believe it rational to apply this complex of methods for the Danube nearshore area-a dynamically changing ecosystem, using phytoplankton's structural indicators and the content of nutrients.…”
Section: Introductionmentioning
confidence: 99%